The Effect of Social Media Use on Body Dissatisfaction in Adolescents - Dewi Yulianti; Anandha Putri Rahimsyah; Gian Sugiana Sugara (Universitas Negeri Surabaya, 2026)
The purpose of this study was to determine the effect of social media use on body dissatisfaction among high school adolescents in Pangandaran Regency. Body dissatisfaction refers to negative feelings and thoughts about one’s physical appearance, often arising from discrepancies between actual and ideal body images. Social media, as a platform that emphasizes visual content, has been identified as a significant contributor to the formation of unrealistic beauty standards that may influence adolescents’ self-perception. This study employed a quantitative correlational design with a simple linear regression analysis technique. The population consisted of 1,507 students from five public high schools in Pangandaran Regency, and a sample of 418 students was selected using stratified random sampling. Research instruments included the Social Media Use Scale and the Body Dissatisfaction Scale, both of which had been tested for validity and reliability. The results of data analysis revealed a positive and significant correlation between social media use and body dissatisfaction (r = 0.212; p < 0.001). The coefficient of determination (R²) = 0.045 indicates that 4.5% of the variance in body dissatisfaction can be explained by social media use. These findings suggest that higher social media engagement is associated with greater body dissatisfaction among adolescents.